2020
DOI: 10.1155/2020/7294574
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital in Old People Living with HIV Is Associated with Quality of Life: A Cross-Sectional Study in China

Abstract: Objective. Old people living with HIV (PLWH) are experiencing a lower quality of life (QoL) than their younger counterparts and have received insufficient attention in China. Given that social capital has been proven to be effective in improving QoL in other countries, we aimed to examine the association between social capital and QoL among old PLWH in China. Methods. The data presented in this study was based on the baseline sample of an ongoing observational prospective cohort study, which was carried out fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Age 70 years or older was negatively correlated with PHS, but positively correlated with MHS. 71 HRQOL studies from Europe found that people ageing with HIV had lower scores in certain HRQOL dimensions than did people of similar age in the general population. Drewes and colleagues 27 found that MHS scores in older people with HIV from Germany were substantially lower than were those among counterparts from the general population.…”
Section: Hrqol Emotional Wellbeing and The Role Of Support Network Am...mentioning
confidence: 99%
See 1 more Smart Citation
“…Age 70 years or older was negatively correlated with PHS, but positively correlated with MHS. 71 HRQOL studies from Europe found that people ageing with HIV had lower scores in certain HRQOL dimensions than did people of similar age in the general population. Drewes and colleagues 27 found that MHS scores in older people with HIV from Germany were substantially lower than were those among counterparts from the general population.…”
Section: Hrqol Emotional Wellbeing and The Role Of Support Network Am...mentioning
confidence: 99%
“…70 A few studies examined the effect of social capital-the resources associated with having a network of relationships of mutual acquaintance or recognition-on HRQOL or mental health outcomes in people with HIV. [70][71][72][73] In the Sichuan Older HIV-Infected Cohort Study, which enrolled people with HIV aged 50 years and older, neither individual or family-based social capital nor community or society-based social capital was associated with PHS scores, whereas both were correlated with MHS scores. Age 70 years or older was negatively correlated with PHS, but positively correlated with MHS.…”
Section: Hrqol Emotional Wellbeing and The Role Of Support Network Am...mentioning
confidence: 99%
“…Social cohesion was higher among the treatment-completed PTB patients. Health outcomes would be improved through social cohesion by reducing the risk of infections and improving health awareness towards healthy behaviour and practices [ 18 , 19 ]. The geographical factor was a major factor as it increased social ties and maintained connection.…”
Section: Discussionmentioning
confidence: 99%
“…2 International Institute of Spatial Lifecourse Epidemiology (ISLE), Hong Kong, China. 3 Department of Family and Preventive Medicine, College of Medicine, University of Arkansas for Medical Sciences, Little Rock, AR, USA. 4 West China School of Public Health and West China Fourth Hospital, Sichuan University, Chengdu, China.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Social capital is defined as the access to and use of resources embedded in one's social networks, 1 which describes trust, solidarity, cooperation, and reciprocity. [2][3][4] The social networks and interpersonal relationships in social capital provide a useful framework for building a health-supporting and healthenhancing environment. 5 Sufficient evidence suggested that social capital is associated with better physical and mental health, mediates the association between socioeconomic inequities and health, 6 and serves as a protective factor against mortality.…”
Section: Introductionmentioning
confidence: 99%